A critical review on various remediation approaches for heavy metal contaminants removal from contaminated soils. (January 2022) - Rajendran, Saravanan; Priya, T.A.K.; Khoo, Kuan Shiong; Hoang, Tuan K.A.; Ng, Hui-Suan; Munawaroh, Heli Siti Halimatul; Karaman, Ceren; Orooji, Yasin; Show, Pau Loke
Abstract: Heavy metal pollution remains a global environmental challenge that poses a significant threat to human life. Various methods have been explored to eliminate heavy metal pollutants from the environment. However, most methods are constrained by high expenses, processing duration, geological problems, and political issues. The immobilization of metals, phytoextraction, and biological methods have proven practical in treating metal contaminants from the soil. This review focuses on the general status of heavy metal contamination of soils, including the excessive heavy metal concentrations in crops. The assessment of the recent advanced technologies and future challenges were reviewed. Molecular and genetic mechanisms that allow microbes and plants to collect and tolerate heavy metals were elaborated. Tremendous efforts to remediate contaminated soils have generated several challenges, including the need for remediation methodologies, degrees of soil contamination, site conditions, widespread adoptions and various possibilities occurring at different stages of remediation are discussed in detail. Graphical abstract: Image 1 Highlights: Impact of heavy metal toxicity towards the environment and human health. Physical, chemical, and bioremediation approaches were used for contaminated soils. Land filling, soil cleaning and solidification methods are well-established. Treatability studies are crucial in the selection of soil sanitation techniques. Future prospect and challenges of remediation would provide insights for readers.